E-002 Efficacy of the Pipeline Embolization Device in the Treatment of Previously-treated Aneurysms. (26th July 2014) - Park, M; Nanaszko, M; Sanborn, M; Moon, K; McDougall, C; Albuquerque, F
Abstract : Introduction: The Pipeline Embolization Device (PED, eV3 Neurovascular, Irvine, California) has increased the ability of the neurointerventionalist to treat progressively more difficult cerebrovascular pathology. We sought to determine the efficacy of the PED in the treatment of the most recalcitrant of aneurysms, those aneurysms recurring after previous treatments. Materials and methods: We retrospectively queried a prospectively maintained endovascular database for previously treated cerebral aneurysms undergoing intervention with the PED from May 2011 to the present time. Twenty-two patients (4 male, 18 female; age range 30–78 yrs, average 59.3 yrs) were treated for 23 aneurysms (average size 11.9 mm, SD 8.5 mm) requiring 29 PED (average 1.3 PED/pt) during the study period. Fourteen patients were originally treated with neuro-interventional procedures (6 coil Embolization, 7 stent assisted coil Embolization, 1 stent only), whereas, eight patients were originally treated with open surgery (7 clipping, 1 wrapping). Of the eight clip recurrences, two patients had an additional neuro-interventional treatment with subsequent recurrence prior to PED use. Average length of follow-up was 8.5 months. Results: The overwhelming majority of all patients in our cohorts had their final angiographic outcomes rated as improved (20 Better, 2 Same, 0 Worse) compared to the pre-procedure state. Furthermore, 11 patients had final Raymond scores of 1 and 11 patients had final Raymond scores of 2. There were no final Raymond 3 angiographic results in the series. Those patients who recurred following initial endovascular treatment had better final Raymond scores when compared to the open surgery cohort (9 of 14 Raymond 1 scores versus 2 of 8 Raymond 1 scores). Conclusions: In our single center series, PED use for the treatment of recurrent aneurysms is an effective means of treating this difficult subset of patients. We observed that the vast majority of these patients will go on to have excellent angiographic outcomes following PED placement. Further investigations are needed to better elucidate the role of the PED in this cohort. Disclosures: M. Park: None. M. Nanaszko: None. M. Sanborn: None. K. Moon: None. C. McDougall: None. F. Albuquerque: None.